New data on the distribution and morphology of the West African squeaker frog Arthroleptis langeri Rödel, Doumbia, Johnson & Hillers, 2009 (Amphibia: Anura: Arthroleptidae) - Nopper, Joachim; Gonwouo, Legrand Nono; Hillers, Annika; Sandberger, Laura; Ohler, Annemarie; Rödel, Mark-Oliver (Zootaxa, 2012)
Arthroleptis langeri Rödel, Doumbia, Johnson & Hillers 2009 is a genetically and morphologically distinct West African squeaker frog species. It was described based on one individual from a forest at 567 m a.s.l. in the East Nimba National Forest, Liberia. However, it was believed to be potentially more widespread in the Western Guinean rainforest ecoregion (Rödel et al. 2009). We herein report on additional specimens of this species. Three frogs were discovered in the collection of the Museum National d’Histoire Naturelle, Paris (MNHN 1998.1779, 1998.1820, 2000.6982; Table 1). These frogs were very similar to the holotype and originated from near the type locality on Mt. Nimba (Seka Valley forest and New Camp forest, respectively; altitudinal data is only provided for MNHN 1998.1820 found at 700 m a.s.l.); the specimens were collected in 1966 and 1969 by Maxime Lamotte. In addition we have recorded a population on top of Mt. Jideh in the Putu Range, south-eastern Liberia (N 5°38’23’’ W °811’8’’), approximately 200 km from the type locality (Fig. 1).